2019
DOI: 10.1007/s40266-019-00655-y
|View full text |Cite
|
Sign up to set email alerts
|

Pimavanserin for Psychosis in Parkinson’s Disease-Related Disorders: A Retrospective Chart Review

Abstract: Background Psychosis is common in Parkinson’s disease-related disorders and is associated with significant morbidity. Pimavanserin is a newly approved treatment for Parkinson’s disease psychosis, but real-world experience with pimavanserin has been limited by small sample sizes and limited assessment of longitudinal outcomes. Objective The aim was to summarize the clinical experience with pimavanserin in a large cohort of patients with Parkinson’s disease-related psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 26 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…In addition, administering pimavanserin in the evening successfully averted daytime sedation. It is worth noting that sedation was not among the most frequent AEs reported in the pivotal phase 3 trial of pimavanserin (i.e., AEs occurring in ≥5% of patients in either treatment group) [ 38 ]; however, a medical center chart review of patients who received pimavanserin reported that “somnolence” was the second most common AE, occurring in 3 patients (3%) [ 43 ]. Among the other notable features in this case series, a nonpharmacological approach was applied that included alleviating life stresses and improving environmental factors such as lighting to reduce the risk of hallucinations; however, this approach must be balanced against the potentially more effective modality of antipsychotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, administering pimavanserin in the evening successfully averted daytime sedation. It is worth noting that sedation was not among the most frequent AEs reported in the pivotal phase 3 trial of pimavanserin (i.e., AEs occurring in ≥5% of patients in either treatment group) [ 38 ]; however, a medical center chart review of patients who received pimavanserin reported that “somnolence” was the second most common AE, occurring in 3 patients (3%) [ 43 ]. Among the other notable features in this case series, a nonpharmacological approach was applied that included alleviating life stresses and improving environmental factors such as lighting to reduce the risk of hallucinations; however, this approach must be balanced against the potentially more effective modality of antipsychotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized trial and double-blind study, the efficacy of risperidone and clozapine in decreasing the symptoms of psychosis was similar while risperidone can aggravate extrapyramidal symptoms [ 51 ]. In addition, all 172 PD subjects in a retrospective study who were receiving an average daily dose of 1.5 mg risperidone had experienced aggravation of extrapyramidal symptoms [ 86 ].…”
Section: Management Of Parkinson’s Disease and Its Associated Psychosismentioning
confidence: 99%
“…Although pimavanserin was generally well-tolerated by many patients in several studies, some adverse reactions were reported. The most common adverse reactions reported for pimavanserin included confusional state, peripheral edema, and hallucinations [ 9 , 86 , 99 ]. Furthermore, QT-interval prolongation can be induced by pimavanserin and it may or may not cause serious cardiac outcomes [ 9 , 99 ].…”
Section: Management Of Parkinson’s Disease and Its Associated Psychosismentioning
confidence: 99%
See 2 more Smart Citations